Dual-Layer Self-Healing Coatings for Carbon Steel: A Sustainable Approach to Enhanced Performance and Durability - Sitti Shalyza Qasidah Salleh; Puteri Sri Melor Megat Yusoff; Nuur Fahanis Che Lah; Muhammad Yasir (International Journal of Integrated Engineering, 2025)
The industrial sectors are continually searching for durable materials with high resistance to wear. While traditional coatings are commonly used, they tend to deteriorate over time, resulting in costly repairs and negative environmental impact. Therefore, this study investigates the development of single and double-layer smart coating systems designed to enhance both durability and sustainability for carbon steel, particularly in harsh environments. The double-layer smart coating (DL-SC) incorporates benzotriazole and boiled linseed oil within an epoxy matrix. The DL-SC is applied in two layers, while the single-layer smart coating (SL-SC) with the same composition is used for comparison. Characterization techniques, including Fourier transform infrared (FTIR) spectroscopy and field emission scanning electron microscopy (FE-SEM), confirm the successful incorporation of the self-healing agents and corrosion inhibitors into the coatings. Additionally, the adhesion strength of DL-SC retained 68.93% of its adhesion strength after immersion in a 3.5 wt% NaCl solution in contrast to 61.05% for SL-SC and 47.92% for traditional epoxy coatings, which highlights the enhanced durability and long-term sustainability of the double-layer system. The enhanced performance of DL-SC is due to the efficient release of BTA and BLO in response to external stimuli, providing extended protection. In conclusion, the double-layer smart coating provides superior durability and long-term protection for carbon steel compared to single-layer.